The lure of the social : encounters with contemporary artists - Coombs, Gretchen (Intellect Books, 2021)
The Lure of the Social' is an intimate and personal exploration into the key individuals, institutions, and gatherings that make up the field of socially engaged art. In this book of encounters, the reader follows Gretchen Coombs on her journey through what could be considered the most significant shift in art world practices in the last two decades. he book navigates a spectrum: at one end, the author works closely with socially engaged artists as part of her ethnographic research; at the other, she tries to find critical distance from which to write about their art projects and the institutional structures that support their work, such as art schools and conferences. Readers are introduced to artists, their work, and the key debates and issues facing this emergent field. In the course of her study, Coombs analyzes the contradictions and paradoxes of this field of practice and gives expression to the artists working to make art relevant in times of social and political uncertainty.